The Impact of Profitability, Solvency, Good Corporate Governance, and Tax Compliance on Corporate Sustainable Longevity - Muhammad Arif Rahman; Aidina Setiawan Putri; Rafli Endana Wilsony (Universitas 45 Surabaya, 2023)
This research investigates the interconnectedness between profitability, solvency, good corporate governance, and tax compliance concerning corporate sustainable longevity. Employing a purposive sampling technique, data were gathered from key stakeholders within various industries. Utilizing thematic analysis, the study unveiled intricate relationships among the mentioned factors and their impact on the sustained success of corporations. Findings suggest that robust profitability and solvency are crucial for enduring corporate existence, while adherence to good corporate governance principles and tax compliance further enhances long-term sustainability. This study contributes to the understanding of how these multifaceted dimensions collectively influence corporate longevity, providing insights valuable for policymakers, corporate leaders, and stakeholders in fostering sustainable business practices.